Decadal variability of surface incident solar radiation over China: Observations, satellite retrievals, and reanalyses. Issue 13 (14th July 2015) - Wang, Kaicun; Ma, Qian; Li, Zhijun; Wang, Jiankai
Abstract Existing studies have shown that observed surface incident solar radiation (Rs) over China may have important inhomogeneity issues. This study provides metadata and reference data to homogenize observed Rs, from which the decadal variability of Rs over China can be accurately derived. From 1958 to 1990, diffuse solar radiation (Rsdif) and direct solar radiation (Rsdir) were measured separately, and Rs was calculated as their sum. The pyranometers used to measure Rsdif had a strong sensitivity drift problem, which introduced a spurious decreasing trend into the observed Rsdif and Rs data, whereas the observed Rsdir did not suffer from this sensitivity drift problem. From 1990 to 1993, instruments and measurement methods were replaced and measuring stations were restructured in China, which introduced an abrupt increase in the observed Rs. Intercomparisons between observation‐based and model‐based Rs performed in this research show that sunshine duration (SunDu)‐derived Rs is of high quality and can be used as reference data to homogenize observed Rs data. The homogenized and adjusted data of observed Rs combines the advantages of observed Rs in quantifying hourly to monthly variability and SunDu‐derived Rs in depicting decadal variability and trend. Rs averaged over 105 stations in China decreased at −2.9 W m−2 per decade from 1961 to 1990 and remained stable afterward. This decadal variability is confirmed by the observed Rsdir and diurnal temperature ranges, and can be reproduced by high‐quality Earth System Models. However, neither satellite retrievals nor reanalyses can accurately reproduce such decadal variability over China.